2016
DOI: 10.1017/s1355617716000680
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Neuropsychological Functioning in Children and Adolescents with Spina Bifida: Associations with Biopsychosocial Predictors and Functional Outcomes

Abstract: Objectives: The current study examined neuropsychological performance among children with spina bifida (SB) to determine biological and functional correlates of distinct "profiles" of cognitive functioning. Methods: A total of 95 children with SB myelomeningocele (ages, 8-15 years) completed a neuropsychological assessment battery. Hierarchical and non-hierarchical cluster analyses were used to identify and confirm a cluster solution. Hypothesized predictors of cluster membership included lesion level, number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 67 publications
1
38
0
Order By: Relevance
“…Whereas researchers utilized supplementary assessment measures to investigate additional dimensions (e.g., stress, anxiety, depression, cognitive function) that theoretically could impact QOL [36,41,42,45], in our US-based review where an estimated 55 million Hispanics/Latinos live, we found no study that probed cultural aspects (e.g., language, acculturation, immigration, etc.) as potential modifiers on QOL.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Whereas researchers utilized supplementary assessment measures to investigate additional dimensions (e.g., stress, anxiety, depression, cognitive function) that theoretically could impact QOL [36,41,42,45], in our US-based review where an estimated 55 million Hispanics/Latinos live, we found no study that probed cultural aspects (e.g., language, acculturation, immigration, etc.) as potential modifiers on QOL.…”
Section: Discussionmentioning
confidence: 89%
“…Lastly, two studies reported on cognitive function outcomes with regard to QOL. In a study by Wasserman and Holmbeck [41], cognitive ability was assessed using the Wechsler Abbreviated Scale of Intelligence (WASI) and subtests from the Wide Range Achievement Tests 3 (WRAT3), the Cognitive Assessment System (CAS), the Delis Kaplan Executive Function System (D-KEFS), the Test of Everyday Attention for Children (TEA-Ch), the Diagnostic Analysis of Nonverbal Accuracy 2 (DANVA2), and the Comprehensive Assessment of Spoken Language (CASL). The results from this study revealed qualitatively different cognitive profiles among children with SB, which ultimately related to physical QOL.…”
Section: Social Determinant Of Health: Health Care Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wasserman and Holmbeck describe different clusters of cognitive functioning in children with SB based off of lesion level, shunt procedures, seizure history, age, ethnicity, socioeconomic status, and family stress. 19 These clusters are thought to impact independence and quality of life. The children who undergo reconstruction may begin in a different cognitive clustering group than those who do not require this throughout their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Wasserman and Holmbeck describe different clusters of cognitive functioning in children with SB based off of lesion level, shunt procedures, seizure history, age, ethnicity, socio‐economic status, and family stress . These clusters are thought to impact independence and quality of life.…”
Section: Discussionmentioning
confidence: 99%